Desain Interaksi Game Belajar Aksara Lampung Bersama Muli Dengan Metode Collision Detection - Theo Kusuma Pamungkas; Ade Surahman; Zaenal Abidin (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2023)
Lampung script is one of the traditional Indonesian scripts that developed in the south of the island of Sumatra. This script is used to write the Lampung and Malay languages. The Lampung script has a total of 20 main characters. This study aims to find out how to make a game Learning the Lampung script with Muli based on Android with a design that is easy to use and can function as an entertainment medium for learning media and a media for preserving Lampung culture. The method for making this game is collision detection starting from the analysis of design, manufacture and testing. the game model presented is in the form of the noble character as the main character, there is 1 main game, namely matching the Lampung script and 3 learning modes, namely the introduction of the Lampung script, the introduction of children with the Lampung script and the painting of the Lampung script. In making this application using software construct 2. Test results the quality aspect of functionality by 13 respondents showed that the application can perform all its functions correctly so that the software gets the criteria for success test results with a percentage of 97.91%. The results of testing the quality aspect of portability on several versions of Android (Android 5, Android 9, Android 10, Android 11) show that the application can be installed and can run properly so that it gets the criteria for success test results with a percentage of 100%.